#### Answer

$t=6$

#### Work Step by Step

Using the properties of equality, the solution to the given equation, $
4(t-3)-t=6
$, is
\begin{array}{l}
4t-12-t=6
\\\\
4t-t=6+12
\\\\
3t=18
\\\\
t=\dfrac{18}{3}
\\\\
t=6
.\end{array}

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$t=6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.